2011
DOI: 10.3892/ol.2011.493
|View full text |Cite
|
Sign up to set email alerts
|

Association of NAT2 phenotype with risk of head and neck carcinoma: A meta-analysis

Abstract: Abstract. N-acetyltransferase 2 (NAT2) is a key enzyme involved in the metabolism of xenobiotics and plays a significant role in the detoxification of numerous potential carcinogens. According to its acetylation status, NAT2 acetylator may be classified into two phenotypes, rapid and slow. Numerous studies have demonstrated that the polymorphisms of NAT2 were correlated with individual susceptibility to several malignant neoplasms, including head and neck carcinomas (HNC). However, the associations between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the same way CRC along [80,106,[148][149][150][151][152][153][154][155][156][157][158], related to smoking and/or intake of red meat [123,125,129,130,149,[158][159][160][161] or cigarette smoking and prostate cancer [162]. The case of head and neck cancer, some studies also suggest an no significant difference in NAT2 slow, intermediate or fast acetylate [7,29,[72][73][74][75][76][77][78]163]. By analyzing a sample of American Caucasians, Chen, et al (2001) also showed that the risk of developing oral cancer is important, regardless of being fast, intermediate or slow acetylator individual, if the amount of cigarettes (>20 pack/years) or alcohol (>15 drinks/week) intake is high [164].…”
Section: Nat2 Phenotypes Not Show Association In Cancer Susceptibilitymentioning
confidence: 99%
“…In the same way CRC along [80,106,[148][149][150][151][152][153][154][155][156][157][158], related to smoking and/or intake of red meat [123,125,129,130,149,[158][159][160][161] or cigarette smoking and prostate cancer [162]. The case of head and neck cancer, some studies also suggest an no significant difference in NAT2 slow, intermediate or fast acetylate [7,29,[72][73][74][75][76][77][78]163]. By analyzing a sample of American Caucasians, Chen, et al (2001) also showed that the risk of developing oral cancer is important, regardless of being fast, intermediate or slow acetylator individual, if the amount of cigarettes (>20 pack/years) or alcohol (>15 drinks/week) intake is high [164].…”
Section: Nat2 Phenotypes Not Show Association In Cancer Susceptibilitymentioning
confidence: 99%
“…NAT2 alleles cause alterations in the enzyme activity; specifically, the rapid or slow acetylator phenotypes, arising from variations in the corresponding DNA sequences, have been correlated with changes in the enzyme activity and stability (Zheng et al, 2012). NAT2 plays a major role in isoniazid metabolism: the elimination rate of isoniazid is trimodally distributed, depending on the NAT2 phenotype (Kiyohara et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the published articles on the relationship between NAT1 and NAT2 polymorphisms and HNC susceptibility is conflicting [ 22 , 23 ]. The association between the polymorphisms ( NAT1 and NAT2 ) and the HNC risk has been evaluated by one [ 24 ] and four [ 25 , 26 , 27 , 28 ] meta-analyses, respectively. However, these studies were published several years ago with the most recent one being published in 2015.…”
Section: Introductionmentioning
confidence: 99%